2000
DOI: 10.4278/0890-1171-14.5.284
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Transcendental Meditation Program on Government Payments to Physicians in Quebec: An Update

Abstract: The results suggest that the TM technique reduced payments to physicians between 5% and 13% annually relative to comparison subjects over 6 years. Randomized studies are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…Herron and Hillis, 2000 [24], retrospectively compared government payments to physicians for 1418 Quebec health insurance enrollees who practiced the Transcendental Meditation (TM) to payments for 1418 randomly selected and matched enrollees who did not. Long term health outcomes were assumed to be equal for both groups.…”
Section: Introductionmentioning
confidence: 99%
“…Herron and Hillis, 2000 [24], retrospectively compared government payments to physicians for 1418 Quebec health insurance enrollees who practiced the Transcendental Meditation (TM) to payments for 1418 randomly selected and matched enrollees who did not. Long term health outcomes were assumed to be equal for both groups.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed decreased pain perception amongst practitioners of the TM technique [8]. Other studies of large groups of TM practitioners suggest decreased usage of medical services [9,10]. Randomised, controlled studies on TM have shown statistically significant reductions in depression compared with control groups [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the significant role of brain coherence in improving health, delineated by Grakov, has application to understanding why forms of meditation that increase such coherence 5-7 also improve health, 8,9 and may be able to do so when all else fails. 10,11 In the case of sense perception, there is no reason why the assumptions on which VSHA is based, its mathematical model of input and output matrices, should 12 in which olfactory sensation fails in a mystifying way for specific molecules.…”
Section: Discussionmentioning
confidence: 99%